Bleeding-related outcomes of low-risk total placenta previa are equivalent to those of partial/marginal placenta previa - Manabu Ogoyama; Hironori Takahashi; Yosuke Baba; Hiromichi Yamamoto; Kenji Horie; Shiho Nagayama; Hirotada Suzuki; Rie Usui; Akihide Ohkuchi; Shigeki Matsubara; Hiroyuki Fujiwara (Elsevier, 2022)
Objective: To clarify whether "low-risk total PP" patients bleed more than partial/marginal PP patients. Materials and methods: The retrospective cohort study was performed involving patients with PP between April 2006 and December 2018. The placental position was determined by ultrasound. From medical charts, the backgrounds as well as obstetric and neonatal outcomes of PP patients were retrieved. Results: This study included 349 patients with PP, which was classified into three types according to the distance between the placenta and internal ostium: total (n = 174), partial (n = 52), and marginal (n = 123) PP. In total PP patients, three factors (prior CS, anterior placenta, and placental lacunae on ultrasound) significantly increased blood loss at CS, the need for hysterectomy, homologous transfusion (≥10 U), and ICU admission. No significant difference was observed in bleeding-related poor outcomes (rate of blood loss ≥2000 mL, amount of homologous transfusion, need for hysterectomy, and ICU admission) between total PP patients without all three factors: "low-risk total PP patients" and partial/marginal PP patients (19.8 vs. 17.1%; p = 0.604, 3.7 vs. 1.1%; p = 0.330, 1.2 vs. 1.1%; p = 1.000, and 1.2 vs. 1.1%; p = 1.000, respectively). Conclusion: Prior CS, anterior placenta, and placental lacunae on ultrasound were risk factors for a bleeding-related poor outcome in total PP patients. Total PP patients without these three factors showed the same bleeding-related poor outcome as partial/marginal PP patients.